The Effect of Lavender Aromatherapy on Post-Cesarean Section Pain at Rumah Sakit Umum Daerah Sibuhuan - Ritonga, Nurindah Lestari (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2024)
Caesarean section has a greater impact than normal birth. One of the impacts of a Caesarean operation is a condition that causes discomfort to the patient in the form of pain after a Caesarean operation. Pain is a biological response that occurs in post-operative patients. There are several therapies that can reduce pain to increase comfort after a cesarean section such as lavender aromatherapy. The aim of this study was to determine the effect of lavender aromatherapy on pain after caesarean section at Rumah Sakit Umum Daerah Sibuhuan. The research method is quantitative with a quasi-experimental design. Respondents totaled 29 people. The instruments used were questionnaires and diffuser tubes. The questionnaire contains demographic data as well as a pain assessment instrument. The diffuser tube is filled with 200-250 ml of water and given 2-3 drops of lavender aroma for 15-30 minutes. The results of this study showed that 5 people experienced severe pain, 13 people experienced moderate pain and 11 people experienced mild pain. After being given lavender aromatherapy after caesarean section, it was found that 3 people experienced severe pain, 10 people experienced moderate pain, 14 people experienced mild pain and 2 people had no pain.